Hyperacute stroke thrombolysis via telemedicine: a multicentre study of performance, safety and clinical efficacy. Issue 1 (17th January 2022) - Evans, Nicholas Richard; Sibson, Lynda; Day, Diana J; Agarwal, Smriti; Shekhar, Raj; Warburton, Elizabeth A
Abstract : Objectives: Timely thrombolysis of ischaemic stroke improves functional recovery, yet its delivery nationally is challenging due to shortages in the stroke specialist workforce and large geographical areas. One solution is remote stroke specialist input to regional centres via telemedicine. This study evaluates the usage and key metrics of performance of the East of England Stroke Telemedicine Partnership—the largest telestroke service in the UK—in providing hyperacute stroke care. Design: Prospective observational study. Setting: The East of England Stroke Telemedicine Partnership provides a horizontal 'hubless' model of out-of-hours hyperacute stroke care to a population of 6.2 million across a 7500 square mile semirural region. Participants: All (2709) telestroke consultations between 1 January 2014 and 31 December 2019. Main outcome measures: Thrombolysis decision, pre-thrombolysis and post-thrombolysis stroke severity (National Institutes of Health Stroke Scale, NIHSS), haemorrhagic complications, and hyperacute pathway timings. Results: Over the period, 1149 (42.4%) individuals were thrombolysed. Thrombolysis rates increased from 147/379 (38.8%) in 2014 to 225/490 (45.9%) in 2019. Median (IQR) pre-thrombolysis NIHSS was 10 (6–17), reducing to 6 (2–14) 24-hour post-thrombolysis (p<0.001). Post-thrombolysis haemorrhage occurred in 27 cases (2.3%). Over the period, median (IQR) door-to-needle time reduced from 85 (65–108) min to 68 (55–97.5) min (p<0.01), driven by improved imaging-to-needle times from 52.5 (38–72.25) min to 42 (30.5–62.5) min (p<0.01). However, the same period saw an increase in median onset-to-hospital arrival time from 77.5 (60–109.25) min to 95 (70–135) min (p<0.001). Conclusions: The results from this large hyperacute telestroke cohort indicate two important points for clinical practice. First, telemedicine via a hubless horizontal model provides a clinically effective and safe method for delivering hyperacute stroke thrombolysis. Second, improved door-to-needle times were offset by a concerning rise in prehospital timings. These findings indicate that although telemedicine may benefit in-hospital hyperacute stroke care, improvements across the whole stroke pathway are essential.